2013
DOI: 10.1111/j.1755-3768.2012.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve head morphology in young patients after antiglaucomatous filtering surgery

Abstract: . Purpose:  To compare the optic nerve head appearance in glaucomatous eyes before and after marked reduction of intraocular pressure (IOP). Methods:  The hospital‐based observational case‐series study included selected glaucoma patients for whom optic disc photographs taken before and 1 week to 5 months after surgical reduction of IOP were morphometrically examined. Results:  The study included 23 eyes of 16 patients (mean age: 28.7 ± 6.0 years). Mean preoperative IOP was 31.6 ± 7.7 mmHg (22–52 mmHg), and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The constancy of macular Bruch´s membrane length and the increase in the fovea-disc border distance by an enlargement of parapapillary gamma zone may imply that Bruch´s membrane is not strongly fixed on the underlying sclera through the choroid. Such a theory of a sliding Bruch´s membrane has also been discussed in a previous study in which the parapapillary region, presumably gamma zone, showed a marked decrease in size after a profound reduction in intraocular pressure for several months had occurred [ 37 ]. The concept of a Bruch´s membrane sliding by the swamping choroid on the sclera does not contradict a firm and stable relationship between Bruch´s membrane, the retinal pigment epithelium and the photoreceptors as basis for a stable visual function.…”
Section: Discussionmentioning
confidence: 90%
“…The constancy of macular Bruch´s membrane length and the increase in the fovea-disc border distance by an enlargement of parapapillary gamma zone may imply that Bruch´s membrane is not strongly fixed on the underlying sclera through the choroid. Such a theory of a sliding Bruch´s membrane has also been discussed in a previous study in which the parapapillary region, presumably gamma zone, showed a marked decrease in size after a profound reduction in intraocular pressure for several months had occurred [ 37 ]. The concept of a Bruch´s membrane sliding by the swamping choroid on the sclera does not contradict a firm and stable relationship between Bruch´s membrane, the retinal pigment epithelium and the photoreceptors as basis for a stable visual function.…”
Section: Discussionmentioning
confidence: 90%
“…The finding that the length of Bruch´s membrane as measured from the posterior pole to the end of parapapillary beta/gamma zone and the finding of an increase in the fovea-disc border distance by an enlargement of parapapillary gamma zone may imply that Bruch´s membrane is not firmly fixed on the underlying sclera through the choroid but may slightly slide. Sliding of Bruch´s membrane has already been discussed in a previous study in which parapapillary gamma zone markedly decreased in size after a profound reduction in intraocular pressure had occurred [ 27 ]. As an analogy, a sliding of the retinal pigment epithelium on Bruch´s membrane has recently been proposed to be involved in the etiology of parapapillary atrophy in glaucoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 9 observed a folding of the RPE and a sliding of the end of RPE on BM under acute IOP elevation, which was associated with a transient enlargement of the peripapillary beta zone. Moreover, Panda-Jonas et al 34 observed changes in areas of peripapillary gamma zone in young glaucoma patients after marked surgical reduction of IOP. Our model showed that ONH deformations induced by eye movements are comparable or larger than those induced by a transient IOP 35 or CSFP increases 36 (see Supplementary Material SC), indicating a potential role for ocular movements in the development and progression of peripapillary zones.…”
Section: Discussionmentioning
confidence: 99%